Simulasi Pengaruh Diameter Poros dalam Analisis Rotordinamik - Mubarak, Amir Zaki (Jurnal Teknik Mesin Unsyiah, 2013)
Vibration analysis of rotor system has been widely performed by numeric method along with the development of computer technology. By the use of the technology, the analysis of the dynamic characteristic of a rotor system has been investigated. The objective of this study is to investigate the influence of shaft diameter to the dynamic characteristic of a rotor system. The investigation is conducted by using computer program simulation. The study is conducted for four system rotor models with a variation of number of disks. Each model has one rotor shaft which is numerically divided into several line elements. The simulation result shows the natural frequencies of the rotor models.